Latin American vertical peripherals: a new paradigm of the urban sustainable development. - Guerrero Torrenegra, Alejandro (Universidad Católica de Pereira, 2016)
In this article is approached the urban-historical development of the Latin American cities, which are characterized by the formation of formal and informal typological genes. It is proposed as main objective, to describe the urban-historical development of Latin American cities, from the formation of vertical informal settlements. The methodological strategy is based on the theories of different authors; through the literature review, using a kind of descriptive, documentary research; with a nonexperimental, transversal design. Finally, it is proposed that the Latin American verticals peripheries have been treated in a paternalist, tangential, generalist limiting compression of social / spatial segregation that tend to dilute and fragment the urban fabric produce the constructions and self-managed reconstruction, without planning.